Body Image and Sexual Desire in the Context of Gender Affirming Therapy: Results of a Cross-sectional Multi-centered Transgender Study. Issue 5 (4th July 2021) - Garz, Maria; Schröder, Johanna; Nieder, Timo; Becker, Inga; Biedermann, Sarah; Hildebrandt, Thomas; Briken, Peer; Auer, Matthias; Fuß, Johannes
Abstract: It has been posited that gender-affirming treatment (GAT) can have an influence on body image and sexual desire in trans people. This study aims to examine associations between GAT and sexual desire as well as whether body image mediates the influences of gender-affirming hormone therapy (GAHT) or gender-affirming surgery (GAS) on sexual desire. A total of 210 individuals diagnosed with gender dysphoria (n = 105 of each gender) were assessed via self-assessment questionnaires in a cross-sectional study. Associations between GAT and sexual desire were investigated via multivariate analyses of variance. Mediation analyses were conducted to clarify associations between GAHT/GAS, body image, and sexual desire. GAHT was associated with increased sexual desire only in transmen. GAS had no significant effect on sexual desire in transmen and transwomen. Body image did not mediate the influence of GAHT or GAS on sexual desire in both groups. GAHT and GAS had significant direct effects on body image in both genders, whereas body image showed no significant direct effect on sexual desire. The results indicate that effects of GAT on sexual desire seem to be attributable to other factors than body image, such as the hormonal influence of testosterone in transmen.